A função do recurso à droga na psicose: enlaces e desenlaces - Júlia Reis da Silva Mendonça (2018)
This Doctoral thesis aims to investigate the function of drug use in psychosis based on two clinical cases. Although the function of substance use in psychosis is described in psychoanalytic literature, mostly, as stabilizing, by promoting an imaginary identification to the signifier "I am a drug addict", some clinical cases show that the use of drugs is not a clinical solution to be sustained, either because of the precariousness of this solution, which places the subject at the limit of the passage to the act, or because the drug does not always have a stabilizing function. In this sense, it develops, in the present research, the hypothesis that the function of the recourse to the substance in the psychosis is not necessarily stabilizing. The research uses the methodology of the construction of the clinical case in order to present the cases as well as to guide the issues that have emerged throughout the research. From the research work carried out, we conclude that the stabilization by the imaginary identification of the signifier "I am a drug addict" in the psychosis is precarious and unstable, that is, it is a solution that is subject to derangements. The contributions of the nodal clinic and the clinic of ordinary psychoses allow us to resituate the investigation of the function of the recourse to the substance in the psychosis in function of the links and disconnections in relation to the Other. In this way, the use of substance in psychosis can promote a disconnection, reinforces the foreclosure, and promotes devastating effects on the body, and even function as one of the worst names. So a possible treatment for psychotics who resort to the substance if delineates towards building new solutions which have less effects than the drug, which are more effective and less harmful to the subjects.